A review of abusive supervision research. (7th August 2013) - Martinko, Mark J.; Harvey, Paul; Brees, Jeremy R.; Mackey, Jeremy
Summary: This paper reviews studies concerned with abusive supervision and provides a constructive revision of Tepper's 2007 model. As a result of our review of the recent research, we revised the 2007 Tepper model and added additional variables and casual paths to increase its explanatory potential. The model we propose distinguishes between abusive supervisory behavior and abusive supervisory perceptions, suggesting that each of these variables needs to be studied separately until we know more about how they are related. The revised model also explicitly recognizes possibilities for reverse causation and stresses the importance of subordinates' individual differences such as attribution style, negative affectivity, and implicit work theories, which have the potential to account for significant variability in subordinates' perceptions of abuse. Suggestions for future research based on the original relationships identified by the Tepper review as well as the variables and causal paths suggested in the revised model are provided. Copyright © 2013 John Wiley & Sons, Ltd.